2002
DOI: 10.4314/jfta.v7i3.19240
|View full text |Cite
|
Sign up to set email alerts
|

Performance of different strains of <i>Pleurotus</i> species under Ghanaian conditions

Abstract: The spawn run period, time for first appearance of mushrooms, number of flushes and biological efficiency (yield) of eight different strains of oyster mushrooms grown on composted sawdust of Triplochiton scleroxylon K (Schum) were studied. The spawn run period on the compost bags for the strains ranged from 40-48 days. Plewotus citrinopileatus strain PCB showed very poor and patchy growth and the mycelium never fully colonised the substrate. This indicates that the different strains of the mushrooms utilize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…Effect of different levels of supplementation of maize flour and wheat bran on growth of Pleurotus ostreatus mushroom. The current findings corresponds to the results observed by (Obodai & Vowotor, 2002) who reported that fruiting bodies of Pleurotus eous strain Kapak became apparent within 4 days. These also corresponds to findings by Rühl et al (2008) who reported 4 days for pinhead formation of Pleurotus ostreatus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Effect of different levels of supplementation of maize flour and wheat bran on growth of Pleurotus ostreatus mushroom. The current findings corresponds to the results observed by (Obodai & Vowotor, 2002) who reported that fruiting bodies of Pleurotus eous strain Kapak became apparent within 4 days. These also corresponds to findings by Rühl et al (2008) who reported 4 days for pinhead formation of Pleurotus ostreatus.…”
Section: Discussionsupporting
confidence: 93%
“…This corresponds to our lowest TP for the first flush. Obodai and Vowotor (2002) reported that the Pleurotus quebeca strain PQB took 35 days. This corresponds closely to 18% WB (36 days) for flush 3.…”
Section: Discussionmentioning
confidence: 99%
“…The yield obtained was found to be very lower than Shah et al, (2004) but superior than others. Obodai and Vowotor (2002) obtained 25.5g of mean yield Pleurotus ostreatus. Kurakkan and sorghum spawns expressed superior values than Obodai and Vowotor (2002).…”
Section: Yield Mean Yield and Yield Ratiomentioning
confidence: 94%
“…Obodai and Vowotor (2002) obtained 25.5g of mean yield Pleurotus ostreatus. Kurakkan and sorghum spawns expressed superior values than Obodai and Vowotor (2002). Further Bano and Srivastava (1962) noticed 22 g of total fresh weight when spawned with paddy spawn.…”
Section: Yield Mean Yield and Yield Ratiomentioning
confidence: 94%
“…The EM-1 strain is widely accepted and cultivated in commercial quantities in Ghana because of its high biological efficiency, shelf-life, taste and yield. It is cultivated all year round and readily adapts to changes in environmental conditions (Obodai and Vowotor, 2002).…”
Section: Introductionmentioning
confidence: 99%